Theory of voting as interdisciplinary research area: political science dimension - Авксентьєв, А. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article researches the voting theory as an interdisciplinary direction, problem field of which applies, in particular, to political science. The category of «voting» and its essential attributes are being determined, the political institutionalization of the practice and its further evolution are analyzed. As part of the modern theory of voting 6 methodological approaches are being singled out: mathematical, political and economic, political, comparative, sociological, electoral and legalspatial; the basic principles and the specificity of these research traditions are researched.